Special model wax for high-temperature alloy and preparation method thereof

By using raw materials such as paraffin and reasonable proportions, special model wax for high-temperature alloys was prepared, which solved the problems of insufficient dimensional stability and low flexural strength of existing model waxes in high temperature environments, and achieved higher thermal stability and size Accuracy.

CN119431999AInactive Publication Date: 2025-02-14QINGDAO XIN NUO KE NEW MATERIALS TECH DEV CO LTD

Patent Information

Application Number
CN202411759370.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-02-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing model waxes are insufficient in dimensional stability, large thermal expansion coefficient and low flexural strength in high temperature environments, which limit their application in high-temperature alloy casting.

Method used

Paraffin, polyether polyol, antioxidant 1076, C5 hydrogenated petroleum resin, melamine polyphosphate, filler and polyethylene wax micropowder are used as raw materials, and special model wax for high-temperature alloys is prepared through reasonable proportioning and process treatment.

Benefits of technology

The bending strength, thermal stability and dimensional stability of the model wax are improved, the linear shrinkage rate and thermal deformation are reduced, and the stability and accuracy of the model wax in high-temperature alloy casting is ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005167189620000111
    Figure BDA0005167189620000111
  • Figure BDA0005167189620000121
    Figure BDA0005167189620000121
Patent Text Reader

Abstract

The invention discloses special model wax for a high-temperature alloy and a preparation method of the special model wax. The special model wax comprises the following raw material components in parts by weight: 15-45 parts of paraffin, 5-25 parts of a crystallization accelerant, 20-50 parts of tackifying resin, 1-5 parts of an auxiliary stabilizer, 1-3 parts of a flame retardant, 5-8 parts of filler and 1-3 parts of polyethylene wax micro powder. The model wax is prepared by mixing the raw material components. The filler is selected from at least one of ultra-high molecular weight polypropylene, nylon, polyurethane, high molecular polystyrene, graphene oxide, fluorinated graphene oxide and flexible phosphate modified boron nitride. The prepared model wax has the advantages of being good in fluidity, high in bending strength, small in linear shrinkage rate and thermal expansion coefficient and good in size stability, the preparation technology is simple, and the cost is low, so that the model wax special for the high-temperature alloy has wide market prospects, and the requirements of the current market are met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of investment casting, and in particular to a special model wax for high-temperature alloys and a preparation method thereof. Background Art

[0002] High-temperature alloys are key materials in the fields of aerospace, energy equipment, etc., with good high-temperature strength, good oxidation resistance and corrosion resistance, and excellent mechanical properties. In the field of aerospace, high-temperature alloys are mainly used to manufacture hot end components of aircraft engines, which need to maintain performance and stability under extremely high temperatures and pressures; in the field of energy equipment, especially in coal-fired power, gas-fired power, nuclear power and oil and gas extraction environments, high-temperature alloys are often used to manufacture components that withstand high temperatures and corrosive environments.

[0003] Model wax for high-temperature alloys is a material specially used in the precision casting process of high-temperature alloys. It is usually composed of multiple components, including base wax, enhancers, stabilizers, etc. Model wax for high-temperature alloys is often used in the precision casting process of high-temperature alloy parts in the fields of aerospace, energy equipment, etc. Therefore, it is necessary to have excellent high-temperature performance and dimensional stability to meet the requirements for accurate replication of complex parts in the precision casting process. In the field of aerospace, high-temperature alloy parts are often subjected to extreme temperatures and mechanical stresses, so there are strict requirements for the high-temperature performance of model wax. Model wax needs to maintain the stability of shape and size during the casting process to avoid deformation or melting due to high temperature. In addition, in the field of energy equipment, such as the manufacture of gas turbines, high-temperature alloy parts also require model wax to have excellent high-temperature bending strength and low linear shrinkage to ensure the reliability of parts in long-term high-temperature operation.

[0004] CN117655280A discloses a wax mold material for titanium alloy precision casting and a preparation method thereof. The wax mold material provided by the invention comprises the following components by weight: 4-6 parts of rosin, 4-6 parts of low-density polyethylene, 48-50 parts of 58# paraffin wax, 30-32 parts of stearic acid, 2-4 parts of montan wax, 4-8 parts of epoxy resin, and 0.5-1.5 parts of filler; the filler is hexagonal boron nitride. The invention obtains the wax mold material for precision casting by mixing and heating the raw materials and granulating them after cooling.

[0005] CN113857427A discloses a precision casting mold material and a preparation method thereof. The components of the precision casting mold material provided by the invention include a basic wax material, a plasticizer, and a tackifying resin modified by cellulose nanofibers. By modifying the strength and toughness of the tackifying resin by using cellulose nanofibers, a precision casting mold material with balanced plasticity and viscosity properties is prepared. The precision casting mold material provided by the invention has the characteristics of low viscosity, good toughness, high strength, low ash content, excellent comprehensive performance, and can be widely used in the casting of various types of high-precision investment mold precision castings.

[0006] However, existing model waxes have problems such as insufficient dimensional stability at high temperatures, large thermal expansion coefficient, and low bending strength, which limit their application in high-temperature alloy casting. Therefore, it is necessary to develop a new type of high-temperature alloy-specific model wax to solve the problem of insufficient performance of existing model waxes in high-temperature environments. Summary of the invention

[0007] In view of the above-mentioned defects of the prior art, the present invention provides a special model wax for high-temperature alloys, which has moderate viscosity, small cone penetration, small ash content, small linear shrinkage, large bending strength and small thermal deformation, and can ensure that the high-temperature alloy casting wax mold is not easy to deform and break during production, has good dimensional stability and can meet the dimensional accuracy requirements and surface quality requirements of complex precision castings. In addition, the simple preparation process and low cost make the special model wax for high-temperature alloys of the present invention have broad market prospects and meet the requirements of the current market.

[0008] The present invention provides a method for preparing a special model wax for high-temperature alloys, comprising the following steps:

[0009] (1) Weigh corresponding paraffin wax, crystallization accelerator, auxiliary stabilizer, tackifying resin, flame retardant, filler and polyethylene wax powder according to the weight ratio of the proposed formula and set aside;

[0010] (2) melting paraffin at 85-95° C., then adding a crystallization accelerator and stirring until the mixture is molten to obtain a blend A;

[0011] (3) heating blend A to 115-125° C., then adding the auxiliary stabilizer to blend A and stirring for 20-40 min to obtain blend B;

[0012] (4) heating blend B to 135-145° C., then adding tackifying resin, flame retardant, filler and polyethylene wax powder to blend B, and stirring for 20-40 minutes to obtain blend C;

[0013] (5) stirring blend C at 135-145° C. for 55-65 h, then cooling to 115-125° C., adding an auxiliary stabilizer, and continuing stirring for 20-40 min to obtain blend D;

[0014] (6) When the blend D is cooled to 70-75° C., it is granulated and then packaged and stored to obtain a special model wax for high-temperature alloys.

[0015] Preferably, by weight, each raw material component includes:

[0016] 15-45 parts of paraffin wax, 5-25 parts of crystallization accelerator, 20-50 parts of tackifying resin, 1-5 parts of auxiliary stabilizer, 1-3 parts of flame retardant, 5-8 parts of filler, 1-3 parts of polyethylene wax powder

[0017] Preferably, the paraffin wax is selected from at least one of 60# fully refined paraffin wax, 62# fully refined paraffin wax, and 64# fully refined paraffin wax.

[0018] Preferably, the auxiliary stabilizer is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant DLTP, antioxidant 168, antioxidant 264, and antioxidant 300.

[0019] Preferably, the flame retardant is selected from at least one of decabromodiphenylethane, melamine polyphosphate, and DOPO flame retardant.

[0020] Preferably, the crystallization accelerator is selected from at least one of sorbitan fatty acid esters, polyether amines and polyethers.

[0021] Preferably, the tackifying resin is at least one of C5 / C9 copolymer petroleum resin, C9 hydrogenated petroleum resin, C5 hydrogenated petroleum resin, hydrogenated rosin, disproportionated rosin, and polymerized rosin; and the softening point of the tackifying resin is ≤120°C.

[0022] Preferably, the filler is selected from at least one of ultra-high molecular weight polypropylene, nylon, polyurethane, high molecular weight polystyrene, graphene oxide, fluorinated graphene oxide and flexible phosphate-modified boron nitride.

[0023] Furthermore, the filler is a mixture of graphene oxide and flexible phosphate-modified boron nitride in a mass ratio of 1-2:1.

[0024] Furthermore, the filler is a mixture of fluorinated graphene oxide and flexible phosphate-modified boron nitride in a mass ratio of 1-2:1.

[0025] Preferably, the method for preparing fluorinated graphene oxide comprises the following steps, measured in parts by weight:

[0026] 0.5-1.5 parts of graphene oxide are mixed with 15-25 parts of anhydrous dichloromethane, and then ultrasonically treated for 0.5-1.5 hours to obtain a graphene oxide dispersion; then the graphene oxide dispersion is mixed with 2-3 parts of 4-fluorophenol, 4-5 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 2.5-3.5 parts of 1-hydroxybenzotriazole and 3-5 parts of triethylamine, and refluxed at 80-90° C. for 22-25 hours under continuous stirring to obtain a mixture; the mixture is washed with water for 2-3 times, and then washed with anhydrous ethanol for 2-3 times to obtain fluorinated graphene oxide.

[0027] Preferably, the preparation method of the flexible phosphate-modified boron nitride comprises the following steps, measured in parts by weight:

[0028] S1. Add 4.5-5.5 parts of hexagonal boron nitride to 45-55 parts of 4-6 mol / L sodium hydroxide ethanol solution, then heat to 75-80°C, mix and stir for 10-13 hours to obtain a mixed solution A; then vacuum filter the mixed solution A, wash to a pH of 6.5-7.5, and then dry to obtain hydroxylated boron nitride; mix 95-105 parts of ethanol, 8-12 parts of water and 0.5-1.5 parts of silane coupling agent KH550, mix and stir for 8-12 minutes at 23-27°C; then add 20-30 parts of hydroxylated boron nitride, mix and stir at 65-75°C for 9-12 hours, and then dry, wash and vacuum filter to obtain alkylated boron nitride for standby use;

[0029] S2, 45-55 parts of polyethylene glycol 200 and 6-7 parts of boric acid are mixed, and condensed and refluxed at 125-135°C for 2.5-3.5 hours to obtain polyethylene glycol borate; then 100-110 parts of phosphoric acid, 30-40 parts of pentaerythritol and 10-13 parts of n-butanol are mixed, and the mixture is stirred at 100-110°C for 3.5-4.5 hours; then the temperature is raised to 118-125°C, and condensed and refluxed at 118-125°C. Flow for 1.5-2.5 hours to obtain pentaerythritol phosphate; then, 27-30 parts of polyethylene glycol borate and 155-160 parts of pentaerythritol phosphate are mixed, and the mixture is stirred at 48-55° C. for 0.5-1.5 hours; then, the temperature is raised to 110-120° C., and stirring is continued at 110-120° C. for 3.5-4.5 hours to obtain a mixture; the mixture is vacuum distilled to remove excess water to obtain a flexible phosphate for standby use;

[0030] S3. Mix the alkylated boron nitride obtained in step S1 and the flexible phosphate obtained in step S2, and perform ultrasonic treatment at 45-55° C. for 25-35 min; then react at 115-125° C. for 3.5-4.5 h to obtain the flexible phosphate-modified boron nitride.

[0031] The invention also provides a special model wax for high-temperature alloys, which is prepared by the above method.

[0032] The present invention selects paraffin as the basic wax material. Paraffin has high strength and maintains good fluidity in a molten state, so that the mold material can smoothly fill the cavity, reduce the volume change caused by temperature change, and help reduce the linear shrinkage of the model wax.

[0033] Polyether polyol is a polymer with crystallization function. It can promote the crystallization process of paraffin wax. By refining the crystals, it can improve the density and uniformity of the model wax, help improve the bending strength and thermal stability of the model wax, and thus reduce the thermal deformation. In addition, the addition of crystallization accelerators can also reduce the linear shrinkage of the model wax.

[0034] C5 hydrogenated petroleum resin is a light-colored resin with good thermal stability, low average molecular weight and high bonding performance. In model wax, because it is closer to the molecular weight of the wax component, it has good compatibility with other raw material components, which is beneficial to increase the cohesion of the wax material and improve the bending strength. In addition, its good thermal stability helps to reduce the linear shrinkage and thermal deformation of the model wax.

[0035] Antioxidant 1076 is a highly effective antioxidant. In model wax, it is mainly used to prevent oxidation of materials during high-temperature processing. Antioxidant 1076 and fluorinated graphene oxide can prevent the structural degradation of fluorinated graphene oxide at high temperatures and maintain its reinforcing effect, thereby maintaining the mechanical properties of the model wax and improving the bending strength. At the same time, the enhancement of antioxidant properties helps to reduce the thermal deformation of the model wax.

[0036] Melamine polyphosphate is a halogen-free, environmentally friendly flame retardant with high thermal stability and flame retardant properties. When melamine polyphosphate is mixed with flexible phosphate-modified boron nitride at high temperature, its phosphate group may chemically react or form hydrogen bonds with the hydroxyl or phosphate groups on the surface of the flexible phosphate-modified boron nitride, thereby generating a strong interfacial interaction, which helps to form a stable composite structure in the wax matrix, and is beneficial to enhancing the thermal stability of the model wax, thereby reducing the amount of thermal deformation. At the same time, in the model wax, its flame retardant properties help to improve the heat resistance of the model wax and further reduce the linear shrinkage.

[0037] Polyethylene wax powder is a high molecular weight wax with high hardness and wear resistance. In model wax, polyethylene wax can interact with C5 hydrogenated petroleum resin to form a strong physical cross-linking network, increasing the hardness and bending strength of the model. In addition, the addition of polyethylene wax helps to improve the fluidity of the model wax and reduce linear shrinkage and thermal deformation.

[0038] The present invention introduces fluorinated graphene oxide (polymer) as filler, which is conducive to increasing the bending strength and thermal stability of model wax and reducing its linear shrinkage. The fluorinated graphene oxide formed by esterification reaction of 4-fluorophenol and graphene oxide in the present invention improves its thermal properties due to the grafting of 4-fluorophenol, which helps to improve the tolerance of model wax under high temperature environment and reduce the performance degradation caused by thermal decomposition. Meanwhile, fluorinated graphene oxide has lower thermal expansion coefficient and linear shrinkage, and its addition helps to reduce the thermal expansion of the overall model wax material, thereby improving dimensional stability, reducing deformation when used at high temperatures, and helping to reduce the volume shrinkage of model wax during curing, improving dimensional accuracy and reusability. In addition, fluorinated graphene oxide has nanometer-level thickness and high aspect ratio, can provide excellent mechanical reinforcement effect, and the addition of fluorinated graphene oxide can form a solid network structure in model wax, improving its overall bending strength. Compared with graphene oxide, the surface of fluorinated graphene oxide may become more affinity due to the fluorination treatment, which helps the bonding between fluorinated graphene oxide and the model wax matrix, thereby improving the flexural strength of the overall material.

[0039] The present invention introduces flexible phosphate-modified boron nitride, which is beneficial to increase its thermal stability and reduce the thermal expansion coefficient of the model wax. Boron nitride itself has a low thermal expansion coefficient. Since the introduction of flexible phosphate groups can absorb and buffer the stress generated by thermal expansion to a certain extent, the introduction of flexible phosphate-modified boron nitride is beneficial to further reduce the overall thermal expansion behavior of the model wax, thereby improving dimensional stability. At the same time, phosphate has high thermal stability, so the introduction of flexible phosphate groups provides additional chemical stability, which is beneficial to increase the thermal stability of the model wax and reduce the amount of thermal deformation.

[0040] Beneficial effects of the present invention:

[0041] 1. Compared with the prior art, the present invention uses paraffin, polyether polyol, antioxidant 1076, C5 hydrogenated petroleum resin, melamine polyphosphate, filler and polyethylene wax powder as raw materials to prepare special model wax for high-temperature alloys. Through reasonable proportioning, the raw material components are used in coordination, so that the prepared model wax has a smaller linear shrinkage rate and ash content, high bending strength, low viscosity and good thermal stability, is not easy to be thermally deformed, is easy to demold and can be reused. The special model wax for high-temperature alloys prepared by the present invention is not easy to break and deform during the casting production process, can meet the dimensional accuracy requirements and surface quality requirements of the model wax in high-temperature alloy casting, and has broad market application prospects. At the same time, the preparation method of the present invention is simple, low in cost, and highly applicable, and can be used for large-scale production.

[0042] 2. Compared with the prior art, the present invention uses flexible phosphate-modified boron nitride and fluorinated graphene oxide in synergistic use as fillers introduced into model wax. The functional groups on the surfaces of flexible phosphate-modified boron nitride and fluorinated graphene oxide may interact with hydrocarbon chains in hydrogenated petroleum resin to form van der Waals forces or hydrogen bonds, thereby improving interfacial compatibility, enhancing the bonding between fillers and resins, promoting uniform dispersion of fillers in resins, reducing agglomeration, and being beneficial to improving thermal stability and flexural strength. In addition, since flexible phosphate-modified boron nitride and fluorinated graphene oxide have high aspect ratios and layered structures, they play a skeleton role in the composite material, can form a mutually supporting network, improve the overall rigidity and flexural strength of the material, and can limit the shrinkage of the model wax material during the curing process, thereby reducing the overall linear shrinkage rate. DETAILED DESCRIPTION

[0043] Parameters for specific chemical substances used, sources.

[0044] 62# fully refined paraffin wax, grade: 62#, brand: Henan Yuyang Wax Industry;

[0045] Melamine polyphosphate, CAS No.: 15541-60-3;

[0046] Graphene oxide, thickness: 1nm, diameter: 0.5μm, source: Beijing Dekedaojin Technology Co., Ltd.;

[0047] Hexagonal boron nitride, particle size: 1μm, grade: PBN300, brand: Nitrogen Boron Technology;

[0048] Polyether polyol, model: HSH-220, brand: Jiangsu Haian Petrochemical Plant;

[0049] C5 hydrogenated petroleum resin, model: FST-H100, brand: Puyang Hengfeng Petrochemical;

[0050] Polyethylene wax powder, model: TW-F0041, brand: Jiangsu Tianwen.

[0051] Example 1

[0052] A method for preparing a special model wax for high-temperature alloys comprises the following steps:

[0053] (1) According to the weight ratio of the proposed formula, 30 parts of 62# fully refined paraffin wax, 15 parts of polyether polyol, 3 parts of antioxidant 1076, 40 parts of C5 hydrogenated petroleum resin, 2 parts of melamine polyphosphate, 6 parts of filler and 2 parts of polyethylene wax powder were weighed and set aside;

[0054] (2) Melting 62# fully refined paraffin wax at 90°C, then adding polyether polyol and stirring until molten to obtain blend A;

[0055] (3) Blend A was heated to 120° C., and then 1 / 2 of the total amount of antioxidant 1076 was added to blend A and stirred for 30 min to obtain blend B;

[0056] (4) heating blend B to 140° C., then adding C5 hydrogenated petroleum resin, melamine polyphosphate, filler and polyethylene wax powder to blend B and stirring for 30 min to obtain blend C;

[0057] (5) Blend C was stirred at 140° C. for 60 h, then cooled to 120° C., the remaining antioxidant 1076 was added, and stirring was continued for 30 min to obtain blend D;

[0058] (6) When the blend D is cooled to 73° C., it is granulated and then packaged and stored to obtain a special model wax for high-temperature alloys.

[0059] The filler is a mixture of fluorinated graphene oxide and flexible phosphate-modified boron nitride in a mass ratio of 2:1;

[0060] The preparation method of the fluorinated graphene oxide comprises the following steps:

[0061] 1 part by weight of graphene oxide is mixed with 20 parts by weight of anhydrous dichloromethane, and then ultrasonically treated for 1 hour to obtain a graphene oxide dispersion; then the graphene oxide dispersion is mixed with 2.5 parts by weight of 4-fluorophenol, 4.5 parts by weight of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 3 parts of 1-hydroxybenzotriazole and 4 parts of triethylamine, and refluxed at 90° C. for 24 hours under continuous stirring to obtain a mixture; the mixture is washed twice with water and then washed three times with anhydrous ethanol to obtain fluorinated graphene oxide.

[0062] The preparation method of the flexible phosphate-modified boron nitride comprises the following steps:

[0063] S1. Add 5 parts by weight of hexagonal boron nitride to 50 parts by weight of 5 mol / L sodium hydroxide ethanol solution, then heat to 76°C, mix and stir for 12 hours to obtain a mixed solution A; then vacuum filter the mixed solution A, wash to a pH of 7, and then dry to obtain hydroxylated boron nitride; mix 100 parts by weight of ethanol (95wt%), 10 parts by weight of water and 1 part by weight of silane coupling agent KH550, and mix and stir for 10 minutes at 25°C; then add 25 parts by weight of hydroxylated boron nitride, mix and stir at 70°C for 10 hours, and then dry, wash and vacuum filter to obtain alkylated boron nitride for standby use;

[0064] S2, 50 parts by weight of polyethylene glycol 200 and 6.5 parts by weight of boric acid are mixed, and the mixture is condensed and refluxed at 130° C. for 3 hours to obtain polyethylene glycol borate; then 105 parts by weight of phosphoric acid, 35 parts by weight of pentaerythritol and 12 parts by weight of n-butanol are mixed, and the mixture is stirred at 105° C. for 4 hours; then the temperature is raised to 120° C., and the mixture is condensed and refluxed at 120° C. for 2 hours to obtain pentaerythritol phosphate; then 28 parts by weight of polyethylene glycol borate and 158 parts by weight of pentaerythritol phosphate are mixed, and the mixture is stirred at 50° C. for 1 hour; then the temperature is raised to 115° C., and the mixture is stirred at 115° C. for 4 hours to obtain a mixture; the mixture is vacuum distilled to remove excess water to obtain a flexible phosphate for standby use;

[0065] S3. Mix the alkylated boron nitride obtained in step S1 and the flexible phosphate obtained in step S2, and subject them to ultrasonic treatment at 50° C. for 30 minutes; then react at 120° C. for 4 hours to obtain the flexible phosphate-modified boron nitride.

[0066] Example 2

[0067] A method for preparing a special model wax for high-temperature alloys, which is different from Example 1 in that the filler is a mixture of graphene oxide and flexible phosphate-modified boron nitride in a mass ratio of 2:1;

[0068] The preparation method of the flexible phosphate-modified boron nitride is consistent with that of Example 1.

[0069] Example 3

[0070] A method for preparing a special model wax for high-temperature alloys, which is different from Example 1 in that the filler is flexible phosphate-modified boron nitride;

[0071] The preparation method of the flexible phosphate-modified boron nitride is consistent with that of Example 1.

[0072] Example 4

[0073] A method for preparing a special model wax for high-temperature alloys, which is different from Example 1 in that the filler is fluorinated graphene oxide;

[0074] The preparation method of the fluorinated graphene oxide is consistent with that in Example 1.

[0075] Comparative Example 1

[0076] A method for preparing a special model wax for high-temperature alloys comprises the following steps:

[0077] (1) According to the weight ratio of the proposed formula, 30 parts of 62# fully refined paraffin wax, 15 parts of polyether polyol, 3 parts of antioxidant 1076, 40 parts of C5 hydrogenated petroleum resin, 2 parts of melamine polyphosphate, and 6 parts of filler were weighed and set aside;

[0078] (2) Melting 62# fully refined paraffin wax at 90°C, then adding polyether polyol and stirring until molten to obtain blend A;

[0079] (3) Blend A was heated to 120° C., and then 1 / 2 of the total amount of antioxidant 1076 was added to blend A and stirred for 30 min to obtain blend B;

[0080] (4) heating blend B to 140° C., then adding C5 hydrogenated petroleum resin, melamine polyphosphate, and filler into blend B and stirring for 30 min to obtain blend C;

[0081] (5) Blend C was stirred at 140° C. for 60 h, then cooled to 120° C., the remaining antioxidant 1076 was added, and stirring was continued for 30 min to obtain blend D;

[0082] (6) When the blend D is cooled to 73° C., it is granulated and then packaged and stored to obtain a special model wax for high-temperature alloys.

[0083] The filler is a mixture of fluorinated graphene oxide and flexible phosphate-modified boron nitride in a mass ratio of 2:1;

[0084] The preparation method of the fluorinated graphene oxide is consistent with that in Example 1;

[0085] The preparation method of the flexible phosphate-modified boron nitride is consistent with that of Example 1.

[0086] Comparative Example 2

[0087] A method for preparing a special model wax for high-temperature alloys, which differs from Example 1 in that the filler is graphene oxide.

[0088] Comparative Example 3

[0089] A method for preparing a special model wax for high-temperature alloys, which differs from Example 1 in that no filler is added.

[0090] Test Example 1

[0091] Performance Testing

[0092] The performance testing method of the special high-temperature alloy model wax prepared in Examples 1-4 of the present invention and Comparative Examples 1-3 is as follows:

[0093] Viscosity: Tested according to the method specified in GB / T 14235.1-2018 Investment Casting Low Temperature Film Materials Part 1: Test Methods for Physical Properties;

[0094] Cone penetration: Test according to the method specified in GB / T 269-2023 Cone penetration test of grease and petroleum grease;

[0095] Softening point: Tested according to the method specified in GB / T 14235.1-2018 Investment Casting Low Temperature Film Materials Part 1: Test Methods for Physical Properties;

[0096] Ash content: Tested according to the method specified in GB / T 14235.1-2018 Investment Casting Low Temperature Film Materials Part 1: Test Methods for Physical Properties;

[0097] Linear shrinkage: Tested with reference to the method specified in GB / T 14235.1-2018 Investment Casting Low-Temperature Film Materials Part 1: Test Methods for Physical Properties;

[0098] Thermal deformation: Tested according to the method specified in GB / T 14235.2-2018 Investment Casting Low-temperature Film Materials Part 2: Performance Test Methods;

[0099] Bending strength: Tested with reference to the method specified in the standard GB / T 14235.2-2018 Investment Casting Low Temperature Film Materials Part 2: Performance Test Methods;

[0100] The test results are shown in Table 1 below.

[0101] Table 1 Performance test data of precision casting wax mold materials of various embodiments and comparative examples

[0102]

[0103]

[0104] As can be seen from Table 1, the viscosity of the special high-temperature alloy model wax prepared in Examples 1-4 of the present invention is moderate; the cone penetration (25°C, dmm) is in the range of 3-4.5; the softening point is in the range of 65°C-72°C; the ash content is in the range of ≤0.025; the linear shrinkage is in the range of 0.6-0.75%; the thermal deformation is in the range of 1.2-1.8mm; and the bending strength is in the range of 4-5kgf. The above data show that the model wax prepared in Examples 1-4 of the present application has moderate viscosity, small cone penetration, small ash content, small linear shrinkage, large bending strength and small thermal deformation, which can ensure that the high-temperature alloy casting wax mold is not easy to deform and break during production, has good dimensional stability and can meet the dimensional accuracy requirements and surface quality requirements of complex precision castings.

[0105] By comparing Examples 1-4 and Comparative Examples 1-3, it is found that the linear shrinkage and thermal deformation of Examples 1-4 are less than those of Comparative Examples 1-3, and the flexural strength is better than that of Comparative Examples 1-3, among which Example 1 has the least linear shrinkage and thermal deformation, and the highest flexural strength.

[0106] By comparing the test data of Example 1 and Comparative Examples 1-3, it is found that compared with Example 1, the viscosity, cone penetration, linear shrinkage rate and thermal deformation of Comparative Example 1 without adding polyethylene wax, the Comparative Example with only graphene oxide as the filler and the Comparative Example 3 without adding filler are significantly increased, while the softening point and flexural strength are significantly decreased.

Claims

1. A method for preparing a special model wax for high-temperature alloys, characterized in that: The following steps are involved: (1) Weigh corresponding paraffin wax, crystallization accelerator, auxiliary stabilizer, tackifying resin, flame retardant, filler and polyethylene wax powder according to the weight ratio of the proposed formula and set aside; (2) melting paraffin at 85-95° C., then adding a crystallization accelerator and stirring until the mixture is molten to obtain a blend A; (3) heating blend A to 115-125° C., then adding the auxiliary stabilizer to blend A and stirring for 20-40 min to obtain blend B; (4) heating blend B to 135-145° C., then adding tackifying resin, flame retardant, filler and polyethylene wax powder to blend B, and stirring for 20-40 minutes to obtain blend C; (5) stirring blend C at 135-145° C. for 55-65 h, then cooling to 115-125° C., adding an auxiliary stabilizer, and continuing stirring for 20-40 min to obtain blend D; (6) When the blend D is cooled to 70-75° C., it is granulated and then packaged and stored to obtain a special model wax for high-temperature alloys.

2. The method for preparing a special high-temperature alloy model wax according to claim 1, characterized in that: By weight, the raw material components include: 15-45 parts of paraffin wax, 5-25 parts of crystallization accelerator, 20-50 parts of tackifying resin, 1-5 parts of auxiliary stabilizer, 1-3 parts of flame retardant, 5-8 parts of filler, and 1-3 parts of polyethylene wax powder.

3. The method for preparing a special high-temperature alloy model wax according to claim 1 or 2, characterized in that: The paraffin is selected from at least one of 60# fully refined paraffin, 62# fully refined paraffin, and 64# fully refined paraffin; the auxiliary stabilizer is selected from at least one of antioxidant 1010, antioxidant 1076, antioxidant DLTP, antioxidant 168, antioxidant 264, and antioxidant 300; and the flame retardant is selected from at least one of decabromodiphenylethane, melamine polyphosphate, and DOPO flame retardant.

4. The method for preparing a special high-temperature alloy model wax according to claim 1 or 2, characterized in that: The crystallization accelerator is selected from at least one of sorbitan fatty acid esters, polyether amines and polyethers.

5. The method for preparing a special model wax for high temperature alloys according to claim 1 or 2, characterized in that: The tackifying resin is at least one of C5 / C9 copolymerized petroleum resin, C9 hydrogenated petroleum resin, C5 hydrogenated petroleum resin, hydrogenated rosin, disproportionated rosin, and polymerized rosin; the softening point of the tackifying resin is ≤120°C.

6. The method for preparing a special model wax for high temperature alloys according to claim 1 or 2, characterized in that: The filler is selected from at least one of ultra-high molecular weight polypropylene, nylon, polyurethane, high molecular weight polystyrene, graphene oxide, fluorinated graphene oxide and flexible phosphate-modified boron nitride; the filler is a mixture of graphene oxide and flexible phosphate-modified boron nitride in a mass ratio of 1-2:1; the filler is a mixture of fluorinated graphene oxide and flexible phosphate-modified boron nitride in a mass ratio of 1-2:

1.

7. The method for preparing the special model wax for high temperature alloys according to claim 6, characterized in that: The preparation method of the fluorinated graphene oxide comprises the following steps, measured by weight: 0.5-1.5 parts of graphene oxide are mixed with 15-25 parts of anhydrous dichloromethane, and then ultrasonically treated for 0.5-1.5 hours to obtain a graphene oxide dispersion; then the graphene oxide dispersion is mixed with 2-3 parts of 4-fluorophenol, 4-5 parts of 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride, 2.5-3.5 parts of 1-hydroxybenzotriazole and 3-5 parts of triethylamine, and refluxed at 80-90° C. for 22-25 hours under continuous stirring to obtain a mixture; the mixture is washed with water 2-3 times, and then washed with anhydrous ethanol 2-3 times to obtain fluorinated graphene oxide. ((Special polypropylene).

8. The method for preparing the special model wax for high temperature alloys according to claim 6, characterized in that: The preparation method of the flexible phosphate-modified boron nitride comprises the following steps, measured in parts by weight: S1. Add 4.5-5.5 parts of hexagonal boron nitride to 45-55 parts of 4-6 mol / L sodium hydroxide ethanol solution, then heat to 75-80°C, mix and stir for 10-13 hours to obtain a mixed solution A; then vacuum filter the mixed solution A, wash to a pH of 6.5-7.5, and then dry to obtain hydroxylated boron nitride; mix 95-105 parts of ethanol, 8-12 parts of water and 0.5-1.5 parts of silane coupling agent KH550, mix and stir for 8-12 minutes at 23-27°C; then add 20-30 parts of hydroxylated boron nitride, mix and stir at 65-75°C for 9-12 hours, and then dry, wash and vacuum filter to obtain alkylated boron nitride for standby use; (Special nylon) S2, 45-55 parts of polyethylene glycol 200 and 6-7 parts of boric acid are mixed, and condensed and refluxed at 125-135°C for 2.5-3.5 hours to obtain polyethylene glycol borate; then 100-110 parts of phosphoric acid, 30-40 parts of pentaerythritol and 10-13 parts of n-butanol are mixed, and the mixture is stirred at 100-110°C for 3.5-4.5 hours; then the temperature is raised to 118-125°C, and condensed and refluxed at 118-125°C. Flow for 1.5-2.5 hours to obtain pentaerythritol phosphate; then, 27-30 parts of polyethylene glycol borate and 155-160 parts of pentaerythritol phosphate are mixed, and the mixture is stirred at 48-55° C. for 0.5-1.5 hours; then, the temperature is raised to 110-120° C., and stirring is continued at 110-120° C. for 3.5-4.5 hours to obtain a mixture; the mixture is vacuum distilled to remove excess water to obtain a flexible phosphate for standby use; S3. Mix the alkylated boron nitride obtained in step S1 and the flexible phosphate obtained in step S2, and perform ultrasonic treatment at 45-55° C. for 25-35 min; then react at 115-125° C. for 3.5-4.5 h to obtain the flexible phosphate-modified boron nitride.

9. A special model wax for high temperature alloys, characterized by: Prepared by the method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Precision casting material and preparation method thereof

    CN113857427A

Cited By

  • Special anti-dimpling mold material for large gas turbine casing forming and its preparation method

    CN122702933A